Android-Based Studend Cooperative Application (Case Study of Kopma UMK) - Agung Prasetyo; Ghozali, Muhammad Imam; Sugihartono, Wibowo Harry (Universitas Negeri Padang, 2025)
Many cooperatives in Indonesia still rely on manual systems, resulting in slow processes, inefficiency, and data inconsistencies. To address this issue, an Android-based KOPMA application was developed using the Dart programming language and Flutter framework. The system facilitates management of member data, sales transactions, and savings in a more effective way. Implementation at KOPMA Universitas Muria Kudus demonstrated faster services, reduced data errors, and improved work effectiveness, while also contributing to student entrepreneurship through a modern and integrated system.